Exploring Refugee Administration Systems in Egypt, Jordan, and Uganda: A Comparative Study - El Guindy, Noura (AUC Knowledge Fountain, 2021)
In this study, I compare three refugee administration models in the global south to one another: Egypt’s, Jordan’s, and Uganda’s. This research is conducted at what I believe is a curious moment of history, where host countries in the global south are encouraged by wealthier states to accept aid in exchange for keeping migrants in the south. In these circumstances, refugee administration models in host countries continue to operate, and new political approaches arise, such as the “Jordan Refugee Compact”. The aim of the comparative study is to spot both the successes and failures of each model in the three countries in terms of meeting the states’ obligations as per international law. I also assess new approaches adopted by some states, spot the lessons learned, and conclude by formulating my recommendations for improving further the existing model in Egypt.